QUANTITATIVE PHYTOCHEMICAL SCREENING AND TERMICIDAL ACTIVITIES OF EUPHORBIA TIRUCALLI L. EXTRACTS ON DANIELLIA OLIVERI (ROLFE) HUTCH. AND DALZIEL AND FICUS CAPENSIS THUNB. WOODS - Ekhuemelo, David Oriabure; Agbidye, Francis Sarwuan; Igoche , Blessing (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated effect of Euphorbia tirucalli extracts on Daniellia oliveri and Ficus capensis woods. Wood samples were purchased and processed into 10 cm x 2 cm x 2 cm dimensions, while plant parts collected were oven dried before extraction. E. tirucalli was screened for phytochemicals. Concentrations of 0.5%, 1% and 2% extracts were prepared by serial dilution. Soligum, methanol and untreated wood samples were used as control. Treated wood samples were laid within 6 x 12 metres field at 1 x 3 metres spacing in a Completely Randomized Design (CRD) in a termitarium and data were taken within 8 weeks. Phytochemical results indicated the presence of alkaloids, phenols, tannins, cardiac glycosides, flavonoids and saponins. Percentage absorption of extracts ranged from 47 - 86 % and 94.00 - 50.67 % in D. oliveri and F. capensis, respectively. Percentage retention of extracts ranged from 10.84 - 2.14 kg/m3 and 11.62 - 7.01 kg/m3 in D. oliveri and F. capensis. Soligum treated wood samples were not attacked throughout the period of study. D. oliveri and F. capensis woods treated with 0.5% E. tirucalli methanol extract were not attached on till the 6th and 8th week respectively. The least percentage weight loss of 5.49 % and 28.32 % were recorded for D. oliveri and F. capensis woods treated with soligum, while, 27.5 5 % and 52.50 % weight loss were recorded for F. capensis and D. oliveri woods treated with 0.5% methanol extract. It was concluded that the use o